Navigating Homeschooling, Parenting, and Work During an Educational Emergency: Insights from Kazakhstan - Janet Helmer; Naureen Durrani; Ghazala Mir; Filiz Polat; Nazerke Karimova; Gulmira Qanay (SAGE Open)
Emergencies disrupt education service delivery; recent global political developments, environmental disasters, and the emergence of new diseases underscore the need for governments and education systems to learn from past crises to better prepare for future challenges. This qualitative study captures the perspectives of Kazakhstani parents as they navigated the difficulties posed by the unprecedented COVID-19 pandemic and school closures. Interviews with 30 parents from different social backgrounds, geographical locations, family types, and employment situations revealed significant challenges. Utilizing the Balance Between Risks and Resources and Family Systems Theory, the study found that parents faced job losses, reduced income, and increased childcare responsibilities as schools swiftly transitioned to online learning. Gender inequity was particularly evident, with most educational support falling on mothers, who often felt unqualified to facilitate online schooling. Compounding these issues were poor internet access and the necessity of sharing a single device among multiple family members. Prolonged social isolation left many mothers feeling emotionally drained, with confined living spaces further impacting their well-being. Educational inequities widened and varied significantly along residential locations. To effectively address future emergencies and the long-term impacts of COVID-19, governments must ensure equitable digital access, provide financial and emotional support to families in need, offer technology training for parents and address unequal gender norms surrounding childcare and domestic labor. These steps will help build a stronger education system that meets the needs of all stakeholders and is better equipped to withstand future crises.